A Comparative Study of Financial Reporting: Assessing Performance and Compliance in Conventional and Islamic Entities - Pratiwi, Nurul Asmi (JURNAL EKONOMI SYARIAH, 2025)
Introduction to The Problem: In an era where financial systems are not only judged by their numbers but also by their values, financial reporting remains fragmented—technically robust yet ethically hollow. Conventional financial statements emphasize profitability and efficiency, while Islamic financial reports aim to integrate moral accountability. However, the absence of a unified evaluative model that embraces both operational soundness and ethical compliance leaves stakeholders with an incomplete picture.Purpose/Objective Study: This study seeks to bridge that gap by presenting a comparative analysis of financial reporting practices in conventional and Islamic entities, focusing on how performance and compliance are reflected, interpreted, and disclosed within each system.Design/Methodology/Approach: Employing a qualitative-descriptive approach, the study analyzes financial reports of representative Indonesian banks—one conventional and one Sharia-compliant. A three-phase methodology is applied: document analysis, comparative matrix construction, and interpretive synthesis. The study benchmarks both performance metrics (liquidity, solvency, profitability) and compliance elements (ethical disclosure, Sharia conformity) using global and Islamic accounting standards.Findings: Findings reveal fundamental philosophical divergences. Conventional reports center on shareholder value, while Islamic reports embody dual accountability—both financial and spiritual. Key distinctions include additional disclosures such as zakat and qardhul hasan, the use of Unrestricted Investment Accounts (URIA), and oversight by Sharia Supervisory Boards. Although conventional banks exhibit stronger profitability, Islamic banks demonstrate higher ethical transparency and resilience. The study proposes an integrative evaluative framework, enabling stakeholders to assess financial health alongside social and spiritual integrity.Paper Type: Research Article